2018
DOI: 10.1128/aac.01590-17
|View full text |Cite
|
Sign up to set email alerts
|

Development of Protective Immunity in New Zealand White Rabbits Challenged with Bacillus anthracis Spores and Treated with Antibiotics and Obiltoxaximab, a Monoclonal Antibody against Protective Antigen

Abstract: The recommended management of inhalational anthrax, a high-priority bioterrorist threat, includes antibiotics and antitoxins. Obiltoxaximab, a chimeric monoclonal antibody against anthrax protective antigen (PA), is licensed under the U.S. Food and Drug Administration's (FDA's) Animal Rule for the treatment of inhalational anthrax. Because of spore latency, disease reemergence after treatment cessation is a concern, and there is a need to understand the development of endogenous protective immune responses fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Only one rabbit (Rabbit 2) in the 1.22 × 10 3 CFU mean daily dose group died of anthrax on Study Day 17.9. Rabbits surviving after an anthrax challenge usually seroconvert by Day 7 with titers increasing to Day 14 post-challenge [20,21]. Rabbit 2 never seroconverted, suggesting an infection was not established until completion of the first 2 weeks of challenges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one rabbit (Rabbit 2) in the 1.22 × 10 3 CFU mean daily dose group died of anthrax on Study Day 17.9. Rabbits surviving after an anthrax challenge usually seroconvert by Day 7 with titers increasing to Day 14 post-challenge [20,21]. Rabbit 2 never seroconverted, suggesting an infection was not established until completion of the first 2 weeks of challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteremia was detected, but below the countable range, in Rabbit 38 that survived inhalation anthrax. One potential explanation for the lack of positive bacteremic measurements may be the presence of measurable bacteremia occurred only during the gap days in the blood collection days (i.e., Study Days 3,[5][6][7][8]10,[12][13][14][15][17][18][19][20][21][22]. Furthermore, most rabbits that succumb to inhalation anthrax from single high-dose exposures have detectable PA levels in the late stage blood samples [14,[22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Using the Animal Rule, efficacy of Anthim ® was evaluated using New Zealand white rabbits [39]. Inhalation of Bacillus anthracis spores cause anthrax infection and, because of the ability of the spores to withstand harsh environments, spores can serve as a source for subsequent infection [40]. Another interesting study, performed after approval, showed that Anthim ® could also prevent these types of infections, which further bolstered the product's utility [40].…”
Section: Antibacterial Antibodies-previous Successmentioning
confidence: 99%
“…Inhalation of Bacillus anthracis spores cause anthrax infection and, because of the ability of the spores to withstand harsh environments, spores can serve as a source for subsequent infection [40]. Another interesting study, performed after approval, showed that Anthim ® could also prevent these types of infections, which further bolstered the product's utility [40]. Later Antibiotics 2020, 9, 155 4 of 12 that year, in October of 2016, the FDA approved the second antibody for bacterial infection, Zinplava™ (bezlotoxumab), for Clostridum difficile infections in adults [41].…”
Section: Antibacterial Antibodies-previous Successmentioning
confidence: 99%
“…The authors dis-cussed the effects of the antibody-based therapy and problems with evaluation of the therapy effi cacy using an animal model. Testing of a new drug called Obiltoxaximab, which is a chimeric monoclonal antibody against protective antigen of anthrax toxin proved some effect and improved the chance to survive the infection (59)(60)(61)(62). The drug is under clinical trials.…”
Section: Anthrax Therapymentioning
confidence: 99%